Peralihan Sarana Pemasaran UMKM Secara Digitalisasi Pasca New Normal - Samariadi, Samariadi; Renata, Daffa Angri; Hakim, Fadwa; Ramadhina, Fanya; Andini, Mia; Mutmainah, Mutmainah; Pungkassari, Nurlaila; Akbar, Pajar Aidil; Aisah, Siti; Afriansyah, Tedy (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2022)
Micro Small and Medium Enterprises (MSMEs) are productive businesses owned by individuals or business entities that have met the criteria as micro-enterprises. This journal was created with the aim of providing information and increasing knowledge about the role of MSMEs in advancing the economy in Pekan Arba Village, Indragiri Hilir Regency, Riau Province. The weaknesses faced by MSMEs in improving their business capabilities are very complex and include various indicators, one of which is interrelated with each other, among others; lack of capital both in quantity and source, lack of managerial ability and operating skills in organizing and limited marketing. The role of Micro, Small and Medium Enterprises (MSMEs) can improve the prosperity of the community, because the existence of MSMEs is able to meet the economic needs of the family, is able to reduce unemployment and is able to meet the needs of the community.